Isolation, identification and characterization of pentacholorophenol degrading bacterium - Gan, Bee Koon (2013)
Pentachlorophenol (PCP) is a wide spectrum biocide applied in agriculture, industry and public health. PCP is lethal to all forms of life due to its nature to inhibit oxidative phosphorylation. Moreover, it is recalcitrant to biodegradation due to the stable aromatic ring and high chlorine content. Thus, the extensive use of PCP has led this chlorophenolic compound becoming a common environmental contaminant. The degradation of PCP is very important since it is highly toxic and carcinogenic. This study was conducted to isolate and characterize a potential PCP-degrading bacterium. The study also included the effectiveness of cell immobilization in enhancing PCP degradation by the bacterial cells as well as protecting the cells from the toxic effect of heavy metals which is the common co-contaminants at the sites of contamination. A potent PCP degrading bacterium has been isolated in this work. The bacterium was identified as Klebsiella sp. and assigned as Klebsiella sp. strain GBK1 based on 16S rDNA phylogenetic analysis. The 16S rDNA sequence has been submitted to genbank under the accession number FJ958193. The optimal PCP degradation conditions occurred at 30°C, pH 7 with 0.3 to 0.4 gL-1 ammonium chloride and 0.6% (w/v) glucose as supplemental carbon source. Klebsiella sp. strain GBK1 was able to degrade PCP with elevated concentration as high as 800 mgL-1. The efficiency of PCP degradation by Klebsiella sp. strain GBK1 was enhanced by immobilization with gellan gum as compared to freely suspended cells. Immobilized Klebsiella sp. strain GBK 1 best degraded PCP with gellan gum concentration of 0.75% (w/v), bead size of 5 mm diameter (estimated surface area of 78.54 mm2) and bead number of 500/100 ml medium. Degradation of PCP by both immobilized and free cells exhibited similar profile characteristics at lower concentrations of PCP. At higher concentration of PCP, the use of immobilized Klebsiella sp. strain GBK 1 resulted in rapid and extensive PCP degradation (degraded PCP up to 1750 mg/L) compared to free cells system whose PCP degrading ability is inhibited at concentration of 900 mg/L. Generally, the rate of PCP degradation was higher in immobilized Klebsiella sp. strain GBK1 and it is more tolerant to high concentrations of PCP (as high as 1750 mg/L). Also, the immobilized cells are more resistant towards heavy metals including As, Zn, Cr, Cd,Cu, Ni, Ag, Pb and Hg (as high as 20ppm) as compared to the free cells system whose activity were affected by 1ppm of heavy metals. In conclusion, Klebsiella sp. strain GBK1 is a potent candidate for bioremediation of PCP and its derivatives at chlorophenols contaminated sites and cell immobilization system was shown to be a more powerful system for biodegradation as compared to freely suspended cells system.